Novel ncRNAs transcribed by Pol III and elucidation of their functional relevance by biophysical approaches - Gavazzo, Paola; Vassalli, Massimo; Costa, Delfina; Pagano, Aldo (Frontiers in Cellular Neuroscience, 2013)
In the last decade the role of non coding (nc)RNAs in neurogenesis and in the onset of neurological diseases has been assessed by a multitude of studies. In this scenario, approximately 30 small RNA polymerase (pol) III–dependent ncRNAs were recently identified by computational tools and proposed as regulatory elements. The function of several of these transcripts was elucidated in vitro and in vivo confirming their involvement in cancer and in metabolic and neurodegenerative disorders. Emerging biophysical technologies together with the introduction of a physical perspective have been advantageous in regulatory RNA investigation providing original results on: a) the differentiation of neuroblastoma (NB) cells towards a neuron-like phenotype triggered by NDM29 ncRNA b) the modulation of A-type K+ current in neurons induced by the small ncRNA 38A and c) the synthesis driven by 17A ncRNA of a GABAB2 receptor isoform unable to trigger intracellular signalling. Moreover, the application of Single Cell Force Spectroscopy to these studies suggests a correlation between the malignancy stage of NB and the micro-adhesive properties of the cells, allowing to investigate the molecular basis of such a correlation.